COVID-19 PANDEMIC AND THE ECONOMIC RESULTS OF AGRICULTURE IN THE EUROPEAN UNION - Stanišić, Tanja; Lazarević, Sonja; Pantić, Nemanja; Leković, Miljan (Economics of Agriculture, 2022)
The Covid-19 pandemic has brought numerous economic challenges to countries around the world. The specificities of certain economy sectors determined the character and intensity of the impact of this health crisis on their results. The purpose of the paper is to analyse the impact that the Covid-19 pandemic has had on the economic results of agriculture in the European Union countries. Comparative analysis and cluster analysis are used in the research. The general conclusion of the paper is that the Covid-19 pandemic did not change the economic importance and role of agriculture in the individual European Union countries. In addition, the European Union countries diﬀer significantly according to the impact of the Covid-19 pandemic on the contribution of agriculture to gross domestic product, while a significant diﬀerence between the countries has not been determined according to the impact of the pandemic on the contribution of agriculture to employment.